Thirty-five years of ISLA on form-focused instruction: A methodological synthesis. (July 2019) - Sok, Sarah; Kang, Eun Young; Han, ZhaoHong
This article offers a methodological synthesis spanning 35 years of instructed second language acquisition research on the efficacy of form-focused instruction. Eighty-eight (quasi-) experimental studies were sampled from six academic journals: Applied Linguistics, Language Learning, Language Teaching Research, Modern Language Journal, Studies in Second Language Acquisition, and TESOL Quarterly . The focus of analysis was on five sets of variables: (1) research design, (2) participants, (3) context in which the studies were conducted, (4) instructional treatment, and (5) outcome measures. Results revealed that since Norris and Ortega's (2000) seminal study, the research domain has grown, not only with respect to the number of studies published, but also with regard to the addition of previously unexamined L1 groups, increase in the number of studies investigating implicit instruction, greater use of multiple measures of learning, and more pretesting and delayed posttesting. However, a number of methodological weaknesses have also persisted.